Effects of preslaughter handling approach and aging on carcass and meat quality attributes in goats - Suliman, Gamaleldin M.; Al-Owaimer, Abdullah N.; Alobre, Mohsen M.; Swelum, Ayman A.; Algaradi, Maged A.; Ba-Awadh, Hani; Sazili, Awis-Qurni; Kumar, Pavan; Kaka, Ubedullah (Elsevier BV, 2024)
This study aimed to assess the impact of preslaughter handling method and aging on carcass and meat quality traits in goats. Twenty-seven male goats of Ardi breed were assigned into three treatment groups viz., the control (C), ear pulling (EP), and hind-leg pulling (HP). The carcasses were stored for post-mortem aging periods of 1, 7, and 14 days. On day 0 and the respective aging days, samples of the Longissimus thoracic et lumborum (LTL) muscles were collected and examined for various meat quality parameters. The preslaughter handling of goats significantly increase the total bacterial count, total Enterobacteriaceae count, and total Clostridium count. It also had a significant effect on the pH of LTL muscle during aging. A significantly lower values for pH were recorded in the treatment groups (EP and HP) as compared to the pH of the C group on day 1 of aging. Notably, both treatment groups were found to increase the shear force, hardness, and chewiness of the meat, ultimately compromising its quality. The proper treatment of meat animals, especially goats, is crucial for enhancing carcass and meat quality. Careful preslaughter handling practices by avoiding ear and hind-leg pulling can minimize negative impacts on the final product. Therefore, the significance of conducting this study lies in its potential to enhance animal welfare, improve meat quality, boost economic benefits for producers, and foster consumer confidence in meat products.